In-Vitro Antimicrobial Activity of Fruits Extract of Embelia ribes Burm. - Khan, Mohammad Alam (International Journal of Pharmaceutical & Biological Archive, 2010)
Embelia ribes is a medicinal plant used intraditional Indian medicine for the treatment of various ailments. This plant was selected to evaluate their potential antibacterialactivity. To determine antibacterial activity and phytochemicals in the crude extracts of this medicinal plant used in traditionalIndian medicine for the treatment of various ailments like rheumatism, piles fever, skin diseases and snake bite. The antibacterial activity of aqueous and ethanolic extracts of this plant was determined by disc diffusion and broth dilution techniques against gram-positive bacterial strains (Bacilus subtilis, Staphylococcus aureus) and gram-negative bacterial strains (Escherichia coli, Pseudomonas aeruginosa). Results revealed that the aqueous and ethanol extracts of Embelia ribes exhibited significant antibacterial activity against gram-positive and gram-negative strains with minimum inhibitiory concentration (MIC) ranging from 1.5 to 100 mg/ml. The most susceptible organism to the ethanolic extract was B. subtilis and P. aeruginosa. The presence of phytochemicals such as alkaloids,tannins, triterpenoids, steroids and glycosides in the extracts of this plant supports their traditional uses as medicinal plants forthe treatment of various ailments. The present study reveals potential use of these plants for developing new antibacterial compoundsagainst pathogenic microorganisms.